1998
DOI: 10.1021/np980140a
|View full text |Cite
|
Sign up to set email alerts
|

Pyranocoumarins from Tropical Species of the Genus Calophyllum:  A Chemotaxonomic Study of Extracts in the National Cancer Institute Collection

Abstract: (+)-Calanolide A, a novel dipyranocoumarin from the Malesian tree Calophyllum lanigerum var. austrocoriaceum, and a closely related compound, (-)-calanolide B, isolated from Calophyllum teysmannii var. inophylloide, are representatives of a distinct class of nonnucleoside HIV-1 specific reverse-transcriptase inhibitor under development as an AIDS chemotherapeutic. NCI repository specimens totalling 315 organic extracts from 31 taxa of Calophyllum were analyzed for related pyranocoumarins using a simple TLC sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
51
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(59 citation statements)
references
References 27 publications
1
51
0
1
Order By: Relevance
“…Since then, the chemical constituents of Calophyllum species have been actively studied (Patil et al 1993;Taylor et al 1994;Currens et al 1996;Zembower et al 1997;McKee et al 1998;Ishikawa 2000;Sekino et al 2004). Systematic studies of the chemical constituents of Calophyllum plants have been conducted by our group, and we showed that C. brasiliense Camb.…”
Section: Introductionmentioning
confidence: 59%
“…Since then, the chemical constituents of Calophyllum species have been actively studied (Patil et al 1993;Taylor et al 1994;Currens et al 1996;Zembower et al 1997;McKee et al 1998;Ishikawa 2000;Sekino et al 2004). Systematic studies of the chemical constituents of Calophyllum plants have been conducted by our group, and we showed that C. brasiliense Camb.…”
Section: Introductionmentioning
confidence: 59%
“…This genus is well known to be a rich source of bioactive xanthones [1][2][3][4], coumarins [5][6][7], chromanone acids [8][9][10][11], and flavonoids [12]. Some these were reported to exhibit of biological activities including anti-HIV, anticancer, antimalarial and antimicrobial [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…This genus has been shown to possess a number of secondary metabolites such as xanthones [1][2][3], coumarins [4,5], and chromanone acids [6,7]. Many of these compounds have shown a wide range of biological and pharmacological properties such as anti-HIV [8,9], anticancer [10,11], and antimalarial properties [12].…”
Section: Introductionmentioning
confidence: 99%
“…This genus has been shown to possess a number of secondary metabolites such as xanthones [1][2][3], coumarins [4,5], and chromanone acids [6,7]. Many of these compounds have shown a wide range of biological and pharmacological properties such as anti-HIV [8,9], anticancer [10,11], and antimalarial properties [12]. In continuation of our phytochemical investigation on bioactive xanthone, we wish to report the isolation and structural elucidation of a new pyranoxanthone, 5,9,11-trihydroxy-10-(2″-hydroxy- In continuation of our phytochemical investigation on bioactive xanthone, we wish to report the isolation and structural elucidation of a new pyranoxanthone, 5,9,11-trihydroxy-10-(2 -hydroxy-3 -methylbut-3 -en-1-yl)-2,2-dimethyl-3-(2 -methylbut-3 -en-2 -yl)-2H,12H-pyrano[2,3-a]xanthen-12-one ( Figure 1) from the stem bark of Calophyllum pseudomole.…”
Section: Introductionmentioning
confidence: 99%